(untitled) - Pavla Kudlová; Ilona Kočvarová (University of Ostrava, 2020)
Aim: To ascertain quality of life in patients with ulcer affected diabetic foot (UADF), and to establish whether there was a relationship between respondentsʼ gender, age, duration and type of treatment for DM, duration of treatment for and etiology of wound, intensity of pain, degree of UADF, method of off-loading pressure on the foot, and quality of life. Design: A cross-sectional study. Methods: A cross-sectional study was conducted on 167 patients with UADF. The data were acquired using the SF-36 and Wound-QoL questionnaires. Exploratory Regression analysis was used during the study as a descriptive technique. The model was realized using the ENTER method. Results: Of the patients who participated in this study, 68% were men and 32% women, their average age was 65 years, and the length of DM treatment was 19 years, with variations in DM treatment, UADF intensity, etiology, and size and degree of UADF, according to Wagner classification. Based on the values of beta coefficients, we can state that according to the SF-36, the main negative predictors of quality of life are: 1) DM treatment; 2) pain intensity; 3) age; 4) wound etiology; and 5) use of wheelchair. Whereas, according to the Wound-QoL, the main negative predictors of quality of life are: 1) DM treatment; 2) pain intensity; 3) size of the wound; 4) age; and 5) use of crutches. Conclusion: Although the results of the two models are similar in certain respects, there are also differences, explained by the fact that two different conceptions of measuring quality of life, with different scoring systems, were involved. Use of the Wound-QoL questionnaire proved particularly effective.